Liderazgo de la Cooperativa de Transporte Urbanos “Fluminense” en la ciudad de Babahoyo periodo 2021. - Sisa Siza, Ninfa Elizabeth (2022)
The objective of this work is to analyze the leadership process in the "Fluminense" Urban Transport Cooperative in the period 2021, taking into account that the leader is essential for the company because he is the most qualified person in terms of training and commitment. with its functions. To know the problems that arise in the company, which allowed us to conduct an interview with the administrative staff, to obtain the necessary information at the time of giving a correct analysis. The results obtained show that one of the causes is the lack of optimal leadership in the work environment, because the manager does not meet the characteristics of a good leader, which causes when coordinating with the respective activities that are presented. in the cooperative.